Theoretico-methodological approaches to analysis social responsibility - Вітковська, І. М. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2018)
The article is devoted to the review of basic theoretical and methodological approaches to analysis social responsibility as one of the important phenomena of modern society. The concept «social responsibility» is analyzed from the standpoint of existential, Marxist, ethical and discursive-communicative approaches. In addition, the author proposed to consider the essence of social responsibility in terms of structural-functional and operational approaches. In this connection, the article analyzes the phenomenon of social responsibility within the framework of the theory of social action and the theory of social systems.